2006
DOI: 10.1029/2005gc001054
|View full text |Cite
|
Sign up to set email alerts
|

Global temperature calibration of the alkenone unsaturation index (UK′37) in surface waters and comparison with surface sediments

Abstract: [1] In this paper, we compile the current surface seawater C 37 alkenone unsaturation (U 37 K 0 ) measurements (n = 629, À1 to 30°C temperature range) to derive a global, field-based calibration of U 37 K 0 with alkenone production temperature. A single nonlinear ''global'' surface water calibration of U 37 K 0 accurately predicts alkenone production temperatures over the diversity of modern-day oceanic environments and alkenonesynthesizing populations (T = À0.957 + 54.293(U 37) 3 , r 2 = 0.97, n = 567). The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
406
5
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(434 citation statements)
references
References 81 publications
18
406
5
5
Order By: Relevance
“…Nearly identical relationships were found in a comparison of the U K' 37 of core-top and surface sediments with the mean annual temperature at 0 m in the overlying waters (e.g., Müller et al, 1998;Conte et al, 2006). The calibration equations based on these relationships have been used for assessing sea-surface paleotemperature.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Nearly identical relationships were found in a comparison of the U K' 37 of core-top and surface sediments with the mean annual temperature at 0 m in the overlying waters (e.g., Müller et al, 1998;Conte et al, 2006). The calibration equations based on these relationships have been used for assessing sea-surface paleotemperature.…”
Section: Introductionmentioning
confidence: 80%
“…High U K' 37 -based temperature in the southern Indian Ocean during the last glacial maximum has been interpreted as the lateral advection of warm-water detrital alkenones by the Agulhas Current (Sicre et al, 2005). Other research has attributed the low U K' 37 -based temperature of the suspended particulates in the Brazil-Malvinas Confluence to the lateral advection of cold-water detrial alkenones by the Malvinas Current (Rühlemann and Butzin, 2006;Conte et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of a recognized potential bias in alkenone-based SST reconstructions linked to alkenone production in the thermocline, to the long-distance alkenone advection by oceanic currents and/or to a differential degradation of C37:3 and C37:2 alkenones within the sediment (see discussion in Conte et al, 2006 and references therein), alkenone-based thermometry is widely used as a SST proxy. Since the global core-top calibration equation of Mü ller et al (1998) is remarkably well correlated with annual-mean SST, most of the alkenone-derived SST records are implicitly interpreted in terms of annual-mean SST.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that in regions of strong surface currents, such as the NBC, alkenone temperature reconstructions may be temporally offset from the nominal age of sedimentation given by planktonic foraminifers as a result of fine particle advection (e.g., Benthien andMüller, 2000 andConte et al 2006). Jaeschke et al (2007) address the discrepancy between Mg/Ca-derived SST from Weldeab et al (2006) and their own alkenone-derived SST in the case of the H1 event and suggest that postdepositional resuspension and transport of the alkenones could be a cause, but they did not address the potential for the same discrepancy for the entirety of their record.…”
Section: Periods Of Anomalous Warmth In the Northern Tropical Atlantimentioning
confidence: 99%